2008
DOI: 10.1523/jneurosci.3978-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively Active TRPC3 Channels Regulate Basal Ganglia Output Neurons

Abstract: A hallmark of the GABA projection neurons of the substantia nigra pars reticulata (SNr), a key basal ganglia output nucleus, is its depolarized membrane potential and rapid spontaneous spikes that encode the basal ganglia output. Parkinsonian movement disorders are often associated with abnormalities in SNr GABA neuron firing intensity and/or pattern. A fundamental question remains regarding the molecular identity of the ion channels that drive these neurons to a depolarized membrane potential. We show here th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(148 citation statements)
references
References 51 publications
(91 reference statements)
8
133
2
Order By: Relevance
“…In fact, it must be considered that, although the overt excitatory (to SNOG) or inhibitory (to L-NAME) responses to NO-active drugs always remained separated in all neurons treated with both drugs, at the same time all of these cells showed clear, statistically significant modulation exerted by both NOactive drugs on the neuronal responses to GLU ejection, suggesting the possible involvement of others effectors than sGC. Thus, the observed effects could be the result of cGMP-independent pathways such as direct protein nitrosylation by NO or peroxynitrite formation and subsequent protein nitration and oxidation (Ahern et al, 2002;Yoshida et al, 2006;Zhou et al, 2008). Moreover, it must be observed that, even if a direct effect of the NO-active drug was not evident on the basal neuronal discharge, often (always, in the neurons tested with both drugs) a significant effect was observed on the magnitude of GLU-induced responses.…”
Section: Possible Mechanisms Involved In the No-dependent Modulation mentioning
confidence: 99%
“…In fact, it must be considered that, although the overt excitatory (to SNOG) or inhibitory (to L-NAME) responses to NO-active drugs always remained separated in all neurons treated with both drugs, at the same time all of these cells showed clear, statistically significant modulation exerted by both NOactive drugs on the neuronal responses to GLU ejection, suggesting the possible involvement of others effectors than sGC. Thus, the observed effects could be the result of cGMP-independent pathways such as direct protein nitrosylation by NO or peroxynitrite formation and subsequent protein nitration and oxidation (Ahern et al, 2002;Yoshida et al, 2006;Zhou et al, 2008). Moreover, it must be observed that, even if a direct effect of the NO-active drug was not evident on the basal neuronal discharge, often (always, in the neurons tested with both drugs) a significant effect was observed on the magnitude of GLU-induced responses.…”
Section: Possible Mechanisms Involved In the No-dependent Modulation mentioning
confidence: 99%
“…RNase contamination can be avoided by thorough deactivation and wearing gloves. PCR primer effectiveness should be tested by using total RNA from a brain tissue punch (Zhou et al 2008;Ding et al 2011). …”
Section: Potential False Negative and False Positive Resultsmentioning
confidence: 99%
“…The high sensitivity and selectivity of scRT-PCR allow the detection of low abundance mRNAs (Surmeier et al 1996). Additionally, this method allows the correlation of gene expression with electrophysiological and functional properties in individually characterized neurons (Liss et al 2001;Zhou et al 2008Zhou et al , 2009Ding et al 2011). Based on literature evidence and our experience, this method is applicable to every neuron types in the nervous systems.…”
mentioning
confidence: 99%
“…They are for instance, potent blockers of cation and anion channels, and FFA at ≥50 μM is now commonly used to block currents through TRP channels and receptor-operated channels (40). Previous experiments have shown that tonic activation of TRP channels maintains basal firing rate, as well as the regularity of firing, in SNr neurons (47). Lee et al (46) tested whether the decrease in firing rate caused by application of the nonselective TRPC and TRPC3 channel blocker, FFA, would persist following catalase-induced H 2 O 2 depletion.…”
Section: Catalase and Trp Channels In Substantia Nigra And Parkinson'mentioning
confidence: 99%